A new genus of Pexicopiini (Lepidoptera: Gelechiidae) for “Gelechia” acanthopis Meyrick, 1932, with review of functional morphology of male genitalia in allied genera - Sohn, Jae-Cheon; Ponomarenko, Margarita G.; Sakamaki, Yositaka (Zootaxa, 2019)
The systematic status of Gelechia acanthopis Meyrick, 1932 is reviewed. The general and functional morphology of the male genitalia merits a new genus in Pexicopiini, Sitotrogoides gen. nov., for G. acanthopis. The musculoskeletal apparatus of the male genitalia in Sitotrogoides is described for the first time and compared with allied genera. The taxonomic position of the genus Sitotrogoides is determined within the tribe Pexicopiini. The lack of the muscle m3 is suggested as a characteristic associating Sitotrogoides with Sitotroga and differing from all other genera in Pexicopiini. The type species of Sitotrogoides, Gelechia acanthopis Meyrick is redescribed. Our new records of Sitotrogoides acanthopis from Korea suggest its extended distribution out of Japan.